(untitled) (Ameghiniana, 2013)
Abstract. Taphonomic analyses were carried out on six sites from the Riversleigh World Heritage Area fossil deposits of northwestern Queensland, Australia. The six sites range in age from late Oligocene to late Miocene and possibly younger. A diverse fossil fauna has been found at these sites, but in this study, only mammalian remains were considered. The aim was to assess the biological and ecological information obtainable from these sites in anticipation of a palaeoecological study of the sites. To determine if fossils from each site were locally derived, specimens were examined for abrasion, breakage, weathering, evidence of digestion or scavenging, and skeletal part representation. Age-class distribution analysis of several peramelemorphians and a subfamily of macropodids was carried out for one of the sites to determine if the mortality profile might be attritional or catastrophic. Vertebrate remains from the six sites are disarticulated and, in combination with the lack of bone weathering, this suggests rapid burial in moist conditions. The majority of specimens are unweathered, unabraded, have a wide range of transport potentials and, at this stage, are not suspected to have significant predator/scavenger biases. These sites are therefore interpreted to be autochthonous assemblages. The age-class distribution analysis indicates attritional accumulation, however exact duration of accumulation can not be ascertained. Resumen. TAFONOMÍA DE LOS SITIOS FÓSILES DEL ÁREA DE RIVERSLEIGH WORLD HERITAGE (OLIGOCENO-MIOCENO), AUSTRALIA. Se realizó un análisis tafonómico en seis sitios de los depósitos del área Riversleigh World Heritage en el noroeste de Queensland, Australia. Los seis sitios abarcan edades desde el Oligoceno tardío al Mioceno tardío y posiblemente más jóvenes. Se ha encontrado allí una diversa fauna fósil pero en este estudio solamente los mamíferos son considerados. El objetivo fue evaluar la información biológica y ecológica quese podía obtener para esos sitios antes de llevar a cabo un estudio paleoecológico. Para determinar si los fósiles de cada sitio fueron derivados localmente, se examinó el material en busca de evidencias de abrasión, fractura, meteorización, digestión o carroñeo y representación de partes esqueléticas. El análisis de distribución de varios peramelemórfidos y una subfamilia de macropódidos fue realizado para cada uno de eses sitios para determinar si el perfil de mortalidad puede ser atricional o catastrófico. Los restos de vertebrados de los seis sitios están desarticulados y, en combinación con la falta de meteorización de los huesos, esto sugiere un rápido enterramiento en condiciones húmedas. La mayoría de los ejemplares no está meteorizado ni presenta abrasión, tiene una amplio espectro de potenciales de transporte y, en esta etapa, no se sospecha que tengan un sesgo especial por depredadores o carroñeros. Por lo tanto, se los interpreta como conjuntos autóctonos. La distribución de las clases etarias indica una acumulación atricional pero su exacta duración no puede ser establecida.